ANALISIS PERLUASAN MAKNA KANJI YANG MEMILIKIBUSHU “月”(TSUKI, NIKUZUKI, FUNAZUKI) - Yanti, Martina Fitri Yanti Fitri; Isnaini, Zuli Laili Isnaini Laili; Aibonotika, Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Kanji is an originally letter from China and spread to Japan. One of kanji element is Bushu. This research is about elaboration meaning of kanji that has character月 (tsuki, nikuzuki, and funazuki). The purpose of this research is to easier the classification of kanji that has character月 (tsuki) which mean ‘moon’, 月 (nikuzuki) which mean ‘flesh’ and月 (funazuki) which mean ‘boat’ by describe the original kanji itself.This research uses descriptive method to describe the origin of starch and elaboration meaning of kanjithat has character月 (tsuki, nikuzuki, andfunazuki). In this research used rikusho theory for determining the origin of each kanji, then was determined form the elaboration that occurs in each kanji.Based on the rikusho theory and determination elaboration of meaning, the writer conclude that the character月 (tsuki, nikuzuki,and funazuki) despite having the same shape, but have different origins. This causes the kanji that have character月 (tsuki, nikuzuki, funazuki) also has differents meaning.kanji that has character月 (tsuki) which mean ‘moon’ has elaborated to ‘condition’. At the kanji that has character月 (nikuzuki) which mean ‘flesh’ has elaborated to ‘part of body’. And at the kanji has character月 (funazuki) which mean ‘boat’ has elaborated to ‘glory’. Key Words:bushu, tsuki, nikuzuki, funazuki